2019
DOI: 10.1210/jc.2018-00197
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: GLP-1 Has an Anti-Inflammatory Effect on Adipose Tissue Expression of Cytokines, Chemokines, and Receptors in Obese Women

Abstract: The above-named article by Manning PJ, Dixit P, Satthenapalli VR, Katare R, and Sutherland WHF (J Clin Endocrinol Metab. [published online ahead of print 21 May 2019]; doi: 10.1210/jc.2018-00197) has been withdrawn by the authors. The authors report, “The reason for this decision is that the statistical methodology we used did not adequately limit the impact of outlier data points on our findings. This was evident after reanalysis of the data using a different method.” doi: 10.121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…(14). Previous studies demonstrated liraglutide has anti-inflammatory properties, promotes endothelial protection, reduces ischemia-reperfusion injury and has immunomodulatory activity (22–25). In the present study, we investigated whether liraglutide can alleviate ALI in a murine model of bacterial pneumonia-induced sepsis by regulating surfactant protein expression/secretion and alveolar surfactant homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…(14). Previous studies demonstrated liraglutide has anti-inflammatory properties, promotes endothelial protection, reduces ischemia-reperfusion injury and has immunomodulatory activity (22–25). In the present study, we investigated whether liraglutide can alleviate ALI in a murine model of bacterial pneumonia-induced sepsis by regulating surfactant protein expression/secretion and alveolar surfactant homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Other errors included inappropriate selection of statistical methods ("the model did not include random slopes"; "immortality bias within the findings"; "did not adequately limit the impact of outlier data points"). [45][46][47] Although some retraction notices explained the specific statistical error, other descriptions were nonspecific, providing little insight into the root cause ("the authors discovered statistical errors"). [48] https://doi.org/10.1017/cts.2024.533 Published online by Cambridge University Press…”
Section: Types Of Errorsmentioning
confidence: 99%
“…Similarly, decreases in the expressions of inflammatory cytokines are observed in 3T3‐L1 adipocytes and ATM in vitro. Moreover, a study of female patients with obesity demonstrated that GLP‐1 certainly plays an anti‐inflammatory role in the development of inflammation in adipose tissue and contributes to the increased accumulation of activated proinflammatory CD14 + or CD16 + monocyte/macrophages . Another recent study using the murine monocyte/macrophage cell line RAW264.7 reported that GLP‐1 contributes to macrophage polarization toward M2 as well as the inhibition of the M1 macrophage polarization/inflammatory response .…”
Section: Novel Antidiabetic Drugs Provide New Therapeutic Perspectivementioning
confidence: 99%